2019
DOI: 10.1111/exd.13915
|View full text |Cite
|
Sign up to set email alerts
|

How hormones may modulate human skin pigmentation in melasma: An in vitro perspective

Abstract: Melasma is a common acquired hyperpigmentary disorder occurring primarily in photo‐exposed areas and mainly affecting women of childbearing age. To decipher the role of sex hormones in melasma, this viewpoint reviews the effects of sex hormones on cutaneous cells cultured in monolayers, in coculture, in 3D models and explants in the presence or the absence of UV. The data show that sex steroid hormones, especially oestrogen, can modulate in vitro pigmentation by stimulating melanocytes and keratinocyte pro‐pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 86 publications
3
42
1
1
Order By: Relevance
“…9 This result accordance with the theoretical basis, that longer use of contraceptive pills will increase the incidence of melasma through several mechanism, such as estradiol that play a role on increace the MCR 1 (melanocortin receptor-1) on melanocytes, tyronase level, and mRNA level. 10,11 Tyronase enzyme play a role in the catalytic reaction, change the tyrosine become L3,4 DOPA (dihydroxyphenilalanine), the increase of tyronase will affect the melanin formation to become more and more. Melanogenesis start with oxidation of aminotyrosine acid become Ldihidroksifenilalanin (L-DOPA) and then become dopaquinone.…”
Section: Discussionmentioning
confidence: 99%
“…9 This result accordance with the theoretical basis, that longer use of contraceptive pills will increase the incidence of melasma through several mechanism, such as estradiol that play a role on increace the MCR 1 (melanocortin receptor-1) on melanocytes, tyronase level, and mRNA level. 10,11 Tyronase enzyme play a role in the catalytic reaction, change the tyrosine become L3,4 DOPA (dihydroxyphenilalanine), the increase of tyronase will affect the melanin formation to become more and more. Melanogenesis start with oxidation of aminotyrosine acid become Ldihidroksifenilalanin (L-DOPA) and then become dopaquinone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results also demonstrate that AP is nontoxic to keratinocytes at the low micromolar doses at which it inhibited melanogenesis. Several earlier reports evidence the role of hormones in affecting skin pigmentation [ 11 , 12 , 28 ], and it has been documented that progesterone might be useful in inclusion in oral contraceptives to counteract the development of melasma that is often attributable to estrogens [ 29 ]. A higher expression of progesterone receptor (PR) has been documented in epidermal skin lesions in contrast to healthy skin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melasma, a facial skin disease with abnormally enhanced melanin synthesis, is not uncommon in middle-aged women. It has been hypothesized that in predisposed persons, sex steroid hormones may initiate hyperpigmentation in melasma by amplifying the effects of UV on melanogenesis [32]. In fact, it has been found that estradiol [33] and diethylstilbestrol (DES) [34] upregulate tyrosinase and enhance melanin synthesis in B16 cells.…”
Section: Plos Onementioning
confidence: 99%